Challenges Faced by First Years English Department Students in Using Online Gamification in Basic Grammar Class - Mella Andriani; Delvi Wahyuni (Universitas Negeri Padang, 2023)
The most common online gamification application in Basic Grammar Class at Universitas Negeri Padang are Quizizz, Wordwall, Kahoot!, iSpring, etc. there are challenges of using online gamification as a method of learning Basic Grammar and students faced many internal challenges along with external challenges. The purpose of this study is to know the internal and external challenges faced by English department students in using online gamification in Basic Grammar Class in Universitas Negeri Padang. The research instruments employed are interviews and questionnaire. 94 students enrolled in the basic grammar course responded to the questionnaire, while 9 of them responded to the individual interview session. Furthermore, this study attempts to provide insights into the barriers and challenges that can be considered when integrating the established gamification frameworks. it is possible to conclude that students experienced difficulties when using gamification concerning external and internal challenges. External Challenges are the weaknesses caused by the environment, like a competitive environment, a lack of an internet network, the lecturer assigning too many tasks and assignments, and a lack of time management. internal challenges are Individual weaknesses such as knowledge and attitude. The internal challenges are as follows: a lack of content knowledge, a lack of student preparation, a lack of motivation, a lack of understanding, and a lack of vocabulary.